Loneliness and Burden Perceived by Family Caregivers of Patients With Alzheimer Disease. (10th April 2020) - Bramboeck, Verena; Moeller, Korbinian; Marksteiner, Josef; Kaufmann, Liane
Background: The present study aimed at investigating loneliness and burden experienced by family members caring for relatives diagnosed with Alzheimer disease. Methods: Participants were 40 caregivers of inpatients with Alzheimer disease. Correlation and multiple regression analyses were conducted to investigate whether caregivers' loneliness (uni- and multidimensional) and burden are associated with and predicted by (1) specific caregiver characteristics and/or (2) patients' dementia severity and neuropsychiatric symptoms. Results: Loneliness was significantly correlated with caregivers' sex, age, and living circumstances, while burden was significantly correlated with caregivers' education solely. Regression analyses revealed that caregivers' sex and living circumstances contributed significantly to variance explanation of loneliness (but not burden), while the additional consideration of patient variables did not improve model fit. Conclusions: Loneliness reported by caregivers of relatives diagnosed with dementia is significantly modulated by caregiver (but not patient) characteristics. Notably, both uni- and multidimensional loneliness scales seem to be sensitive diagnostic tools.